त्रिभुवन विश्वविद्यालय नेपाली विषयको विद्यावारिधि (२०७०–२०८२) को विषयक्षेत्र - Thapa, Ashok (Tribhuvan University Journal, 2026)
The doctoral (PhD) research in Nepali at Tribhuvan University began in 2030 BS (1973 AD). This article examines doctoral research studies completed from 2070 to 2082 BS, as a continuation of the previous work that analyzed research conducted until 2070 BS. It examines the subject area of a PhD dissertation in Nepali literature (2070-2080 BS) within the Faculty of Humanities and Social Sciences, TU. Altogether, 84 titles are listed, and those have been finalized for the viva in 7 different subject areas. In this article, a survey method has been used. The 84 titles have been classified into 7 areas and compared to the theme of the thesis finalized before 2070 BS. Bibliometric Analysis Theory was used for this work. In the same way, this research concluded that the majority of the research focused on Nepali Poetry (34.52%), Novels (19.05%), Short Stories (15.48), Dramas (11.90%), Folk literature (9.52%), Language Studies (8.33%), Criticism (1.19%). Compared with titles before 2070 BS, Feminism, Interdisciplinary approach, Subaltern, Trauma, and Identity are newly added research areas. Thus, the research will be a valuable reference for future research, especially for those pursuing doctoral research in the area of Nepali language and literature.